2004
DOI: 10.17221/4078-pse
|View full text |Cite
|
Sign up to set email alerts
|

Study of inheritance of some agronomic and morphological traits in burley tobacco by graphic analysis of diallel cross

Abstract: The mode of inheritance of yield, topping height, leaf number, days to flowering, leaf length and width was studied by means of graphic analysis in a half diallel cross test of four burley tobacco varieties (Saturn, TN 86, Bs 92 and Bols 100) in 1998 and 1999. The trial was set up according to the RCBD at four replications in the experimental field of Tobacco Institute Zagreb in Pitomača. Overdominance in inheritance of all studied traits, except leaf length and width in 1998, was found by the graphic method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
1
12
1
Order By: Relevance
“…The tobacco leaves are manually removed from the plants whilst the plants are in the field, so as to leave the stalks behind, and the leaves are then threaded onto a string to provide approximately 200-500 leaves/m of string material. The string (control group) was then hung allowing the tobacco leaves to be sun-cured for 15 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tobacco leaves are manually removed from the plants whilst the plants are in the field, so as to leave the stalks behind, and the leaves are then threaded onto a string to provide approximately 200-500 leaves/m of string material. The string (control group) was then hung allowing the tobacco leaves to be sun-cured for 15 …”
Section: Methodsmentioning
confidence: 99%
“…According to many studies in oriental tobacco, prevailing mode for inheritance of number of leaves is dominance and partial dominance [12,13]. However, Radoukova et al [14] and Butorac et al [15] reported that in the mode of inheritance of Virginia and Burley tobacco, the most important are dominant and additive gene effects. The variability of quantitative traits of oriental tobacco in different environmental conditions is depending on the individual characteristics of genotype, and needs a specific study of inheritance of D DAVID PUBLISHING…”
Section: Introductionmentioning
confidence: 99%
“…These results are in conformity to the results of Pandia et al (1985), and Gopinath et al (1996), who observed an over dominant gene action for length of leaf. Butarac et al (2004), however, reported that over dominant gene action for length of leaf under irrigated conditions changed to partial dominance under drought while Shoaei and Honarnejad (1996), observed addictive gene action with partial dominance for this trail. Distribution of array points (Figure 6a and b) indicated that the genotype NC89 contained maximum dominant genes while Coker 254 contained the least dominant genes under both conditions.…”
Section: Length Of Leafmentioning
confidence: 98%
“…Thus, expression of plant traits depends upon the action of governing genes under prevailing environment. Butarac (2004) reported additive gene action for leaf area index and length of leaf while they indicated dominant gene action for plant height and width of leaf in tobacco. Shoaei and Honarnejad (1996) found additive gene action for plant height and width of leaf and reported over dominance for plant height, leaf area index and length of leaf.…”
Section: Introductionmentioning
confidence: 99%
“…Sencar and Gokmen (2004) reported that ecology in addition to the ecology has significant impact on the leaf length. The ecology has also been considered an important feature affecting the tobacco yield along with plant height, leaf width and the number of leaves (Butorac et al, 2004;Gixhari and Sulovari, 2010); therefore, investigated as an important feature in many studies conducted on tobacco.…”
Section: Leaf Length (Cm)mentioning
confidence: 99%